Splatoon. Vol. 4 - Hinodeya, Sankichi; Miyaki, Tetsuichiro; Hurley, Jason A., 1981-; Hinodeya, Sankichi (San Francisco, CA : VIZ Media, LLC, 2018)
The preliminary rounds have come to a close! . . . As the Inklings gear up for the main round of the Square King Cup, they must prepare for all kinds of teams that are way stronger than they are, and maybe even have to battle the undisputed Splatoon champion--the player known as Emperor!
Translated from the Japanese.
Based on the hit Nintendo video games--Back cover.
Book reads from right to left in the traditional Japanese format.
Rated A: All Ages; Parental Advisory: Splatoon is rated A and is suitable for all ages--Colophon.
4.0
5-8
Keywords: Contests -- Comic books, strips, etc -- Juvenile fiction; Squids -- Comic books, strips, etc -- Juvenile fiction; Contests -- Fiction; Squids -- Fiction; Humorous comics; Graphic novels; Paintball (Game) -- Juvenile fiction; Manga; Comics (Graphic works)